Produção de alimentos probióticos do tipo não lácteo com células de Lactobacillus acidophilus LA-5 e chocolate - Teixeira, Renata Cristina (2011)
The definition of functional food was born as substances and biologically active components that are added to food which offer the potential of enhanced health. In this way, probiotics are marketed as functional foods and have become increasingly used because of their hole for modify gut microflora and improve health. In present master dissertation, chocolate s probiotic formulations have been developed using lactobacilli with special focus on Lactobacillus acidophilus LA 5. The formulations were evaluated in terms of cell death kinetics, survival, physicochemical and sensory analysis. The obtained results have indicated that: a) chocolate-based products containing lactobacilli can be used for probiotic formulations, but the use of ascorbic acid and vegetable aqueous extract of Camellia sinensis reduced the stability of probiotic tested; b) three fermentation medium tested are adequate for fermentation, but fermentation broth composed by brewer\'s yeast and glucose presented the best results when compared with the others; c) there is difference in taste (p<0.001) among chocolate and probiotics chocolate, but chocolate containing probiotic is accepted by consumers.